Global Art Cinema: New Theories and Histories - Cabañas, Miguel A (Imagofagia, 2021)
Sobre Galt, Rosalind y Karl Schoonover, (Coords.) Global Art Cinema: New Theories and Histories, Oxford: Oxford University Press, 2010, 384 pp., ISBN 9780195385632 Palabras clave: reseña, Rosalind Galt, Karl Schoonover, Global Art Cinema: New Theories and Histories